Extraction and Evaluation of Lepidium Sativum and Flax Seeds Mucilage as a Pharmaceutical Granulation Binder - Nagla Algali Layas; Sumaya O. Aljabri; Aref T. Mohamed; Aisha M. Alshaafi; Amna K. Algondi; Malak M. Alshrif (University of Huddersfield Press, 2021)
The powders are held together by a binder to form granules. Some excipients are of natural origins are currently available as an alternative over the synthetic ones in pharmaceutical formulation. The aim of this study was to isolate the mucilage from different plant seeds and compare them to evaluate the binding effects. In the present study, an effort was made to investigate the efficacy of mucilage obtained from Lepidiumsativum and flax seeds as granules excipients. The mucilage was extracted from selected seeds by the conventional method by precipitation of soaked and blended seeds in acetone. The dried mucilages were subjected to several phytochemical and physicochemical properties. Granules were formulated by wet granulation method by using extracted mucilage as a binding agent and comparisons were made against the granules prepared with standard binder as PVP. The granules are evaluated by various physical properties such as (bulk and tapped densities, Hausner's ratio, Carr's index, angle of repose and friability). The results showed that the granules prepared from extracted mucilage as a binder had good flow and mechanical properties, all evaluated parameters were within the permissible limits. Thus, mucilage could be used as an alternative binding agent in pharmaceutical granules.